Miss Janie's girls [large type] - Brown, Carolyn, 1948- (Center Point Large Print, 2021)
"Miss Janie is at the end of a long and full life, but she has no intention of crossing that finish line until she's found her girls . . . It's been ten years since Teresa and Kayla shook off the dust of Birthright, Texas, went their separate ways, and never looked back. Apart from their foster mom, Miss Janie, they don't have many fond memories of their hometown. Or of each other. Still, neither can forget the kind woman who opened her home and heart to two teenagers in need. When a private investigator -- who just happens to be Miss Janie's handsome nephew -- tracks them both down and tells them Miss Janie is dying, Teresa and Kayla know deep down that they've got to be there for her as she had been there for them. With Teresa and Kayla together again under the same roof, old tensions may flare, but with Miss Janie's help, they might rediscover that home is the perfect place for new beginnings."--